PENGARUH KUALITAS PELAYANAN, PENGIKLANAN DAN HARGA TERHADAP KEPUTUSAN KONSUMEN DALAM MEMILIH GO-FOOD - Faomasi Ndruru -; Trimartha Sihombing -; Fenny Krisna Marpaung - (Jurnal Ekonomi Bisnis Manajemen Prima, 2021)
This study aims to examine and analyze the effect of service quality, advertising and price on consumer decisions in choosing Go-Food. This research was conducted on 24 consumers or Go-Food customers in Medan City. Based on the results of this study, it is known that service quality, advertising and price have a significant positive effect on consumer decisions in choosing Go-Food. Go-Food must be able to maintain or continue to improve the quality of its service, because of the good quality of service, maintain or continue to develop creativity for advertising, and increase price competitiveness, because current prices are able to have a positive influence on consumer decisions to choose Go-Food.